Analytical Characterization and Pharmacokinetic Insight of Bioactive Compounds from Champia parvula and Moringa oleifera for Biocontrol of Blue Mold in Apple Fruits - Eman A. Alwaleed; Mashail N. Alzain; Naglaa Loutfy; Amany A. El-Shahir (Plants)
The present study aimed to identify the active chemical compounds, mainly phenolic acids, of Champia parvula and Moringa oleifera, evaluate the pharmacokinetic properties of their primary compounds, and assess a novel method for the biocontrol of blue mold by evaluating the antifungal activity of both extracts. Gas chromatography (GC) and high-performance liquid chromatography (HPLC) were utilized to identify the active chemical compounds, mainly phenolic acids. GC illustrated the presence of long-chain aliphatic fatty acids like eicosanoic acid with the formation of oct-1-en-3-ol compounds attached. Catechin was the main bioactive component among the several bioactive compounds identified by HPLC analysis, exhibiting favorable pharmacokinetic behavior, including good absorption, distribution, and metabolic stability. According to the findings, both extracts had antifungal activity, but C. parvula extract (100 mg/mL) exhibited the strongest in vitro and in vivo antifungal activity, with the highest percentages of inhibition (disk diffusion method) against Penicillium expansum, Penicillium crustosum, and Talaromyces atroroseus, ranging between 62.67 and 100%. C. parvula extract (100 mg/mL) could fully inhibit the pathogenicity and aggressiveness of the five tested strains in apple fruits (in vivo). In conclusion, the extract from C. parvula and M. oleifera shows potential antifungal properties and a high phytochemical content.